PENGARUH PENERAPAN PENDIDIKAN MULTIKULTURAL TERHADAP TINGKAT TOLERANSI BERAGAMA BERBASIS PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) - Lao, Hendrik A.E; Pa, Hemi D. Bara; Dami, Fredrickson (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Implementing multicultural education is essential in education, as it fosters respectful attitudes among students and promotes a deep understanding of religious tolerance. This study aims to analyze the extent to which the implementation of multicultural education influences the level of religious tolerance at Payeti Christian Middle School, East Sumba Regency. The research employs a quantitative approach, utilizing data collection techniques such as observation, questionnaires, and documentation, and analyzes the data using descriptive statistics with the SPSS 27 application. The results of the study found that the application of multicultural education increased religious tolerance by 33.2% > 5%, which means that Ho was rejected, and Ha was accepted. Thus, multicultural education significantly impacts the degree of religious tolerance, as demonstrated by the P5 initiative at Payeti Christian Middle School in East Sumba Regency. Therefore, the implementation of multicultural education to increase religious tolerance needs to be carried out sustainably.